Perceived Stress Levels and Its Sources Among Doctors and Nurses Working in A Tertiary Care Teaching Hospital, Kancheepuram, Tamil Nadu - Narayanan Sathiya; Rafeeq Ruwaidha; Farooq Salma Nusrath; Farin Fathima; Thandavamoorthy Gomathy; Hegde Kumar Shailendra (Medsci Publications, 2016)
Introduction: Stress and emotional disturbances among doctors and nurses are relatively common, and seemingly, this is a worldwide problem. Recently studies have reported high levels of stress among health care professionals. This study was done to assess prevalence of perceived stress and its sources among doctors and nurses. Methodology: Cross-sectional study was conducted among 200 study subjects (84 doctors & 116 nursing staff) by simple random sampling. Perceived stress scale (PSS 10) questionnaire was used to assess stress scores. Work environment, health related and psycho-social stressors were assessed using a 16 items questionnaire. MS Excel sheet and SPSS were used for data entering and statistical analysis. Results: Prevalence of stress among study participants was found to be 39.5% (79). Mean PSS score among doctors was found to be 18.35 (±4.7) and the same among nurses was 17.16 (±5.5). Inadequacy of staff and resources, sleep deprivation, confronting constant emotional smoking physical suffering were found as important stressors. Conclusions: This study identified that doctors and nurses do face considerable amount of stress at workplace. Appropriate coping strategies must be adopted by them to cope up with this stress.